Implementasi Program Pembagunan Infrastruktur Di Desa Jirene Kecamatan Nogy Kabupaten Lanny-Jaya - Kogoya, Mardi; Pati, Agustinus B.; Rares, Joyce (Sam Ratulangi University, 2023)
This research aims to understand and comprehend the implementation of infrastructure development programs in Jirene Village, Nogy District, Lanny-jaya Regency in 2022. The data used in this research are primary and secondary data. Primary data was obtained through interviews using a prepared interview guide. The data analysis technique used is interactive analysis method. The results obtained regarding infrastructure development in Jirene Village show that the development of infrastructure in Jirene Village is still lagging behind and can be considered suboptimal, as seen from the construction of roads which is perceived as disturbing by the community, even though village budget should prioritize the welfare of the community. From this research, it can also be seen that the perception of the community towards road infrastructure development in Jirene Village is disappointing. The expectations of the community in Jirene Village regarding road infrastructure development are far from reality. The community in Jirene Village believes that the allocated budget for development has not resulted in tangible outcomes.